BUDAYA ORGANISASI MASYARAKAT DALAM PEMBANGUNAN RUMAH DI DESA MOLOMPAR DUA KECAMATAN TOMBATU TIMUR KABUPATEN MINAHASA TENGGARA - RATUELA, FITRI; RORONG, ARIE JUNUS; PALAR, NOVIE ANDERS (JURNAL ADMINISTRASI PUBLIK, 2018)
The organizational culture in Molompar Dua Village is called Mapalus. Culture mapalus inMolompar Dua Village one of which is mapalus house construction. Which where consisting of thirtymembers each member of the mapalus of house building must include building materials and labor. Themethod used is descriptive with qualitative approach. The informants in this study include the Village Headof Molompar Dua, Mapalus Board of House Construction, Member Mapalus House Construction, HostReceiver. Data collection techniques used in the form of interviews, observation and documentation. Dataanalysis is done by data collection, data reduction, data presentation, and conclusionThe results showed that the application of family values must always exist in maintaining togethernessin the mapalus of house construction, the implementation of deliberation and consensus must always putforward the common interest to accept any opinion and the results of the decision can not be disputed. theimplementation of deliberation and consensus in the chairman's house and can be in the guard hall.Cooperation is needed to achieve the goal of building the home mapalus. Unity and unity are important inthe developmental mapalus of the house because with the unity and unity all members can work together, tobuild and complete the homes of the recipient members of the housing mapalus.Suggestion given in this research is if always maintain the value of kinship, deliberation and consensus,cooperation, and unity mapalus development of house to reach organizational goals.Keywords: Organizational Culture, Community, Mapalus, House Construction